Production of liquid fuels from co-pyrolysis of high-density polyethylene (HDPE) and spent coffee grounds: Comparison of microwave energy and liquified petroleum gas as heat source on the fuel properties - Wan Rizki Ansari; Renita Manurung; Iriany; Hamidah Harahap (South African Journal of Chemical Engineering, 2025)
High-Density Polyethylene (HDPE) is one of the most widely used plastic materials. However, its non-degradable nature makes it a persistent pollutant that requires proper management. Pyrolysis has been recognized as a promising technology for converting HDPE waste into value-added products. The efficiency of HDPE pyrolysis can be enhanced through the addition of spent coffee grounds (SCG), a process known as co-pyrolysis. This study aims to evaluate the co-pyrolysis of HDPE and SCG by investigating the impact of heat sources on liquid fuel production. In this research, co-pyrolysis was conducted using microwave and liquefied petroleum gas (LPG) heating, with variations in SCG:HDPE ratios, reaction temperatures, and microwave power. The results indicate that these parameters significantly influence the liquid fuel yield. The highest yield was obtained with an SCG:HDPE ratio of 1:3, for both microwave and LPG heating modes. GC–MS analysis revealed the composition of the liquid fuels, showing that hydrocarbons were the dominant components in both heating methods. The produced liquid fuels comprised organic compounds ranging from C9 to C18. Furthermore, fuel properties were assessed, demonstrating that the microwave-assisted process yielded a higher calorific value (42.11 MJ/kg), thereby validating its effectiveness over LPG heating. This study highlights the advantages of microwave-assisted co-pyrolysis in producing liquid fuels from SCG and HDPE. Further investigations are required to optimize reaction parameters, assess environmental impacts, and evaluate the economic feasibility of scaling up this technology for waste-based biofuel production.